Morphological study of mandible of Sapajus apella monkeys - Cardozo, Bianca; Prado, Felippe; Rossi, Ana; Araujo, Rafael; Freire, Alexandre (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The aim of this study was to evaluate the morphology of the mandible of Sapajus apella monkeys by morphometry. Specifically, to understand the regions and anatomical structures of the forces trajectories of the mandibles of Sapajus apella monkeys.